2006
DOI: 10.2353/ajpath.2006.060006
|View full text |Cite
|
Sign up to set email alerts
|

Individual Cell-Based Models of Tumor-Environment Interactions

Abstract: The presence of scattered tumor cells at the invading front of several carcinomas has clinical significance. These cells differ in their protein expression from cells in central tumor regions as recently shown for the EGF-TM7 receptor CD97. To understand the impact of such heterogeneity on tumor invasion, we investigated tumor cells with modified CD97 expression in vitro and in vivo. Applying an individual cellbased computer model approach, we linked specific cell properties of these cells to tumor invasion ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 42 publications
3
95
0
Order By: Relevance
“…The two molecules shared almost identical EGF-like domains and 50% homology in the stalk and the 7TM regions. As well as functional roles in leukocyte migration, recruitment and activation [18][19][20][21], CD97 is known to be involved in angiogenesis and the migration and invasion of tumor cells [22][23][24]. By analyzing the GPS cleavage of CD97-mFc-fusion protein, we show herein that CD97 and EMR2 have very different GPS cleavage efficiencies.…”
Section: Introductionmentioning
confidence: 84%
“…The two molecules shared almost identical EGF-like domains and 50% homology in the stalk and the 7TM regions. As well as functional roles in leukocyte migration, recruitment and activation [18][19][20][21], CD97 is known to be involved in angiogenesis and the migration and invasion of tumor cells [22][23][24]. By analyzing the GPS cleavage of CD97-mFc-fusion protein, we show herein that CD97 and EMR2 have very different GPS cleavage efficiencies.…”
Section: Introductionmentioning
confidence: 84%
“…All leiomyomas and 9 out of 21 leiomyosarcomas were CD97 positive . The disability of muscular CD97 to bind the ligand CD55 implicates another function in this cell type (Wobus et al, 2004) as the suggested role as an adhesion molecule (Hamann et al, 1996) in tumor cells where CD97 promotes migration capacity (Galle et al, 2006;Steinert et al 2002). Based on these findings, we are eminently interested in CD97 regulatory mechanisms in SMCs.…”
Section: Introductionmentioning
confidence: 94%
“…Several mathematical models have addressed the dynamics of various receptors, such as integrins clustering (Paszek et al, 2009), integrinmediated cell migration (Cirit et al, 2010), E-cadherins signalling in cancer invasion (Ramis-Conde et al, 2008) and colorectal cancer development (van Leeuwen et al, 2009). Other models have handled cell adhesion in a more simplified way as an average adhesion strength between individual point cells (in both lattice-based (Anderson, 2005;Deutsch, 2007;Kim et al, 2009) and lattice-free (Drasdo & Hoehme, 2005;Galle et al, 2006;Norton et al, 2010) models) or as a mean value taken over a patch of tissue modelled as a continuum (Byrne & Chaplain, 1996;Armstrong et al, 2006).…”
Section: Discussionmentioning
confidence: 99%